Corrigendum to “Innovate integration of guided inquiry learning (GIL) and project-based learning (PjBL) to enhance students’ science literacy” - Nova Florentina Ambarwati; Retno Dwi Suyanti; Aaron Loh; Ribka Kariani Br Sembiring; Darinda Sofia Tanjung; Dyan Wulan Sari HS (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
At the request of the authors, the published version of this article has been updated. After publication, the authors conducted a detailed review. They identified several inconsistencies between in-text citations and the reference list, as well as minor inaccuracies and formatting issues in some reference entries. The authors initiated these corrections following their own post-publication review and do not reflect an error on the part of the editorial office. The amendments concern only the accuracy and consistency of citations and references. They do not affect the data, analyses, interpretation, or conclusions of the study. The authors apologise for any inconvenience these issues may have caused to readers and thank the editorial team for facilitating these corrections.